Can law offer certainty and security in today’s world? An outline of a response based on the value of legal certainty - Sánchez Barroso, Borja (Razón y fe, 2019)
The ability of law to provide certainty and security in an increasingly unstable and complex world depends to a large extent on the importance attached to legal certainty. This value is threatened in the current context, given the emergence of a new principle: the imperative of flexibility. Recovering the value of legal certainty, despite the difficulties that this entails, may be the only way to preserve the very nature and function of law.